Ferroptosis regulators related scoring system by Gaussian finite mixture model to predict prognosis and immunotherapy efficacy in nasopharyngeal carcinoma - Liu, Zijian; He, Jinlan; Hu, Xiaolin (Frontiers in Genetics, 2022)
The role of ferroptosis in tumor progression and metastasis has been demonstrated. Nonetheless, potential biological function of ferroptosis regulatory pattern in nasopharyngeal carcinoma (NPC) remains unknown. Ferroptosis regulatory patterns of nasopharyngeal carcinoma samples were evaluated based on 113 ferroptosis regulators and three distinct ferroptosis subtypes were determined by unsupervised clustering. The ferroptosis score (FEP score) was identified to quantify ferroptosis patterns within individual tumors by Gaussian finite mixture model and systematically correlated with representative tumor characteristics. Subtype 1 and subtype 3 were consistent with immune activated phenotype, while subtype 2 was consistent with immune suppressed phenotype. High ferroptosis score, characterized by immune activation and suppression of mRNA based stemness index (mRNAsi) and Epstein-Barr virus (EBV) genes, indicated an immune activated tumor microenvironment (TME) phenotype, with better progression free survival (PFS) and lower risk of recurrence and metastasis. Low ferroptosis score, characterized by activation of Wnt and NF-κB signaling pathways and lack of effective immune infiltration, indicated an immune suppressed tumor microenvironment phenotype and poorer survival. High ferroptosis score was also correlated to enhanced response to immunotherapy, and was confirmed to correlate with therapeutic advantages and clinical benefits in an anti-programmed cell death 1 ligand 1 (PD-L1) immunotherapy cohort. As ferroptosis played a crucial role in the tumor microenvironment’s diversity, assessing the ferroptosis pattern within individual tumor with ferroptosis score could enhance our understanding of tumor microenvironment infiltration characterization and help develop more effective immunotherapy.